Activity of antioxidant enzymes in response to atmospheric pressure induced physiological stress in deep-sea hydrothermal vent mussel Bathymodiolus azoricus. (March 2016) - Martins, Inês; Romão, Célia V.; Goulart, Joana; Cerqueira, Teresa; Santos, Ricardo S.; Bettencourt, Raul
Abstract: Deep sea hydrothermal Bathymodiolus azoricus mussels from Portuguese EEZ Menez Gwen hydrothermal field possess the remarkable ability to overcome decompression and survive successfully at atmospheric pressure conditions. We investigated the potential use of antioxidant defense enzymes in mussel B. azoricus as biomarkers of oxidative stress induced by long term acclimatization to atmospheric pressure conditions. Mussels collected at Menez Gwen hydrothermal field were acclimatized for two weeks in three distinct conditions suitable of promoting physiological stress, (i) in plain seawater for concomitant endosymbiont bacteria loss, (ii) in plain seawater under metal iron exposure, (iii) constant bubbling methane and pumped sulfide for endosymbiont bacteria survival. The enzymatic activities of superoxide dismutase (SOD), catalase (CAT), and iron storage proteins in addition to electrophoretic profiles were examined in vent mussel gills and digestive gland. Gills showed approximately 3 times more SOD specific activity than digestive glands. On the other hand, digestive glands showed approximately 6 times more CAT specific activity than gills. Iron storage proteins were identified in gill extracts from all experimental conditions mussels. However, in digestive gland extracts only fresh collected mussels and after 2 weeks in FeSO4 showed the presence of iron storage proteins. The differences between SOD, CAT specific activities and the presence of iron storage proteins in the examined tissues reflect dissimilar metabolic and antioxidant activities, as a result of tissue specificities and acclimatization conditions influences on the organism. Highlights: A tissue differentiation on antioxidant function is proposed. B. azoricus presents oxidative stress tolerance when deprived of hydrostatic pressure. B. azoricus combine antioxidant scavengers to struggle against a metal enrich environment. Iron storage proteins are present in B. azoricus tissues as part as their physiological systems.